Transition to automated information and control systems for the operational management of transportation in the Russian Railways network: terms of reference - M. I. Mehedov; E. A. Sotnikov; P. S. Kholodnyak; S. V. Lobanov (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. Transportation process experiences continuous and often unpredictable changes in the operational situation at stations, sections and proving grounds of the network. Stabilisation of transportation process requires operative control decisions, which today are made by dispatchers and duty workers of various levels on the basis of knowledge, experience, abilities and intuition using information received at automated work stations from numerous information systems. Development and introduction of automated information and control systems instead of information systems will increase technical and economic efficiency of operational management of transportation and expand the control zones of the duty dispatchers.Materials and methods. The paper proposes to classify factors affecting transportation process as internal and external. It examines the reasons for their formation and the nature of their impact on operational work.Results. The work establishes time parameters for the development of operational control decisions and proves the necessity of technical and economic evaluations in the selection of rational decisions. The work justifies the stages of implementation of information and control systems in terms of selecting the categories of dispatchers and on-duty workers whose automated work stations are subject to priority development as information and control workplaces. The authors consider the conditions for the construction of hierarchical simulation models of the operation of controlled objects for the selection of rational operational control decisions at specific workplaces.Discussion and conclusion. The research results can serve as a basis for the Russian Railways to create a programme for solving the urgent problem of transition from information to automated information and control systems for operational management of transportation process on Russian Railways.